2020
DOI: 10.1186/s40623-020-01185-3
|View full text |Cite
|
Sign up to set email alerts
|

Frictional and structural controls of seismic super-cycles at the Japan trench

Abstract: The diverse mechanical behaviors of subduction zones during the seismic cycle emerge from the nonlinear dynamics of a complex mechanical system with interacting brittle and ductile deformation. The 2011 Tohoku mega-quake represents the culmination of a super-cycle of partial and full ruptures of the plate interface, but the physical controls on the down-dip segmentation of the megathrust remain unclear. Here, we propose a two-dimensional rheological model of the Japan trench to explain the variability of earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 172 publications
3
39
1
Order By: Relevance
“…However, partial coupling and interseismic creep are predominant at the base of the MFT (Supplementary Fig. 3), as is often found at fault bends 8,10,11 . The transition zone between velocity-strengthening and velocityweakening friction is characterised by high stresses (Fig.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…However, partial coupling and interseismic creep are predominant at the base of the MFT (Supplementary Fig. 3), as is often found at fault bends 8,10,11 . The transition zone between velocity-strengthening and velocityweakening friction is characterised by high stresses (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…The development of seismic super-cycles may be controlled by several factors, such as particular frictional properties 5,6 , geometric complexity 7 , off-fault deformation in the hanging wall 8 , and residual stress from past earthquakes 9 . The remaining challenge is to assess the relative contribution of these factors at specific plate boundaries 10,11 .…”
mentioning
confidence: 99%
“…Barbot 17 focused on down-dip segmentation of rupture styles; partial ruptures at the deeper part and a giant, super-cycle rupture at the entire velocity-weakening interface. Barbot 17 presented two-dimensional simulations, which suggested that the rupture styles at the middle segment of the Japan Trench are controlled by both structural and frictional heterogeneity. Therefore, the spatial distributions of slip along the trench may also be explained by structural and frictional heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The earthquake phenomenon includes a wide spectrum of rupture styles associated with different source characteristics (Beroza & Ide, 2011; Barbot, 2019b; Leeman et al, 2016; Scuderi et al, 2017; Obara & Kato, 2016; Veedu & Barbot, 2016). The stress change on a fault produced by an earthquake is one of the fundamental physical properties that govern the seismic cycle, impacting the style of rupture, that is, slow or fast earthquake, and the magnitude of the event (Aki, 1967, 1979; Barbot et al, 2020; Kanamori & Anderson, 1975; Kanamori et al, 1993; Poli & Prieto, 2016; Sobolev et al, 2017; Venkataraman & Kanamori, 2004; Ye et al, 2016a). The scaling relationship between stress drop and various other source parameters depends on the tectonic setting (e.g., Romanowicz, 1992; Scholz et al, 1986; Walsh & Watterson, 1988) and on the rupture style (Beeler et al, 2001; Cocco et al, 2016; Cattania & Segall, 2018; Gomberg et al, 2016; Kato, 2012; Liu‐Zeng et al, 2005; Peng & Gomberg, 2010).…”
Section: Introductionmentioning
confidence: 99%